The use of Google Translate in Indonesian tertiary writing / Shalawati M. Tesol, Naginder Kaur and Sitti Hadijah - M. Tesol, Shalawati; Kaur, Naginder; S., Sitti Hadijah (Universiti Teknologi MARA, Kedah, 2025)
With extensive use of technology inherent in all spheres of language teaching and learning, in the last 20 years or so, Google Translate has increased in prominence and now plays a significant and parallel role in assisting learners with various academic tasks. With its far-reaching presence, questions have arisen as there are concerns and ambivalence as to whether it is able to provide precise guidance in academic work. Thus, this study explores how Google Translate is used by Indonesian tertiary students in writing their research proposal. The central focus of the analysis also extends to investigate students’ perceptions and attitudes towards the use of Google Translate in completing their academic tasks. Taking up from where previous studies have left, this paper looks for unique patterns in the use and support of Google Translate in students’ writing process. To achieve these aims, a qualitative research approach was used to explore in-depth perceptions and opinions of four female students based on their instructors’ analysis of their research proposals, namely, in chapter one where ideas and conceptual terms were evidently present. Results suggest that all students use Google Translate at varying levels for translation of words, sentences and paragraphs. However, the trends of use are dissimilar along different types of search. Some students experienced a reduced dependence on Google Translate from the beginning to end of the semester, while others remained heavily reliant till completion of proposal writing. The study implies the viable role of Google Translate in the teaching and learning of ESL writing and indubitably supports its complementary role in research, education and scholarship in academia.